2010
DOI: 10.1002/jmv.21883
|View full text |Cite
|
Sign up to set email alerts
|

Predicted 30‐year protection after vaccination with an aluminum‐free virosomal hepatitis A vaccine

Abstract: Few studies have examined the duration of protection following vaccination against hepatitis A virus (HAV) with currently licensed HAV vaccines. This study explored the long-term immunogenicity in individuals vaccinated with the virosomal hepatitis A virus, Epaxal. Adult volunteers (N = 130) previously enrolled into four different studies between 1992 and 1994 and who had completed a 0/12-month immunization regimen (primary and booster dose) were asked to participate in this follow-up study. Yearly anti-HAV ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…However, we do not know how far the immunity induced by immunization persists, though several studies reported recently that the vaccine induced immunity last as long as vaccines have been available [19][20][21][22]. Therefore, the heterogeneous endemicity over the country [17,18] raised a serious concern of HAV infection, that is, if immunity induced by vaccination decreases when immunized children become adults, the disease burden from hepatitis A will paradoxically increase, because relatively high levels of circulating hepatitis A virus persist.…”
Section: Discussionmentioning
confidence: 89%
“…However, we do not know how far the immunity induced by immunization persists, though several studies reported recently that the vaccine induced immunity last as long as vaccines have been available [19][20][21][22]. Therefore, the heterogeneous endemicity over the country [17,18] raised a serious concern of HAV infection, that is, if immunity induced by vaccination decreases when immunized children become adults, the disease burden from hepatitis A will paradoxically increase, because relatively high levels of circulating hepatitis A virus persist.…”
Section: Discussionmentioning
confidence: 89%
“…However, with the milder infection and reduced antigen load associated with vaccination vs. natural infection, the level of long-term immunity may require booster vaccination to reset the plateau phase of antibody production to a new set point that resides above the threshold required for protection (Figure 2). Immunization with live, attenuated hepatitis A vaccine or inactivated hepatitis A vaccine are both capable of eliciting long-term antiviral protection [74] but interestingly, a 2-dose vaccination series with an inactivated whole virus hepatitis A vaccine has been estimated to provide more than 30 years of protective immunity in >95% of vaccinees [75]. A recent study examining the duration of antibody responses following 1, 2, or 3 doses of Cervarix, a highly repetitive non-infectious virus-like particle vaccine against human papilloma virus (HPV), is also particularly informative [76].…”
Section: Lessons From Vaccines That Elicit Immunity Of Differing Dmentioning
confidence: 99%
“…A single dose of Epaxal, the only aluminum-free virosomal HAV vaccine currently available, is highly immunogenic (3). Two doses of Epaxal administered 12 months apart give adults a real-time protection of at least 9 to 11 years, which is predicted to last for at least 30 years in Ն95% of individuals (4).…”
mentioning
confidence: 99%